1999
DOI: 10.1016/s0960-9822(99)80483-7
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Ku protein plays a direct role in telomeric silencing and counteracts inhibition by Rif proteins

Abstract: Yku70p/Yku80p, the yeast Ku protein homologue, is a DNA end-binding heterodimer involved in non-homologous end joining. It also binds to telomeres, where it plays an important role in the maintenance of telomeric DNA structure [1] [2] [3] [4] [5]. Ku protein, together with Rap1p, a telomeric DNA (TG(1-3) repeat)-binding protein, is also required to initiate transcriptional silencing, or telomere-position effect (TPE). Here, we provide evidence for a direct role of Ku in TPE, which is most likely to be in eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
123
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(135 citation statements)
references
References 25 publications
12
123
0
Order By: Relevance
“…Genes involved in telomere length regulation often influence the structure of the telomeric heterochromatin, and these changes are sometimes associated with an increase or decrease in the transcription of genes placed adjacent to the telomere (13,33,37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genes involved in telomere length regulation often influence the structure of the telomeric heterochromatin, and these changes are sometimes associated with an increase or decrease in the transcription of genes placed adjacent to the telomere (13,33,37).…”
Section: Resultsmentioning
confidence: 99%
“…The yKu70p͞yKu80p heterodimer influences telomere length by protecting telomere ends from degradation. It also has additional functions in telomeric silencing (through recruiting Sir proteins to the telomeres), telomeric nuclear localization, and telomere replication timing (12)(13)(14)(15). Cdc13p binds the telomeric single strand, recruits telomerase to the telomere, and prevents degradation (16,17).…”
mentioning
confidence: 99%
“…Previous cytological evidence has shown that Rap1p colocalizes with YЈ elements at the telomeres in relatively intact nuclei (Gotta et al, 1996) and that Rif1p and Rap1p generally colocalize in vivo (Mishra and Shore, 1999). In the chromatin spread method, spheroplasts are gently disrupted and their nuclear contents are spread locally on the slide.…”
Section: Colocalization Of Rap1 With Rif1mentioning
confidence: 99%
“…All strains containing the tlc1-476A mutation used in this study were heteroallelic for the TLC1 locus and also contained a wild-type (WT) copy of the TLC1 gene. The W303-1a and RIF1-9xMYC strains used in this study were obtained from David Shore (Mishra and Shore, 1999). Mating, sporulation, and tetrad dissection were done according to standard methods (Fink, 1991).…”
mentioning
confidence: 99%
“…Silencers recruit SIR proteins through the combined action of different DNA-binding factors: the origin recognition complex (ORC) and either or both of two multifunctional regulators, repressor͞activator protein 1 (Rap1p) and ARS binding factor 1 (Abf1p). At telomeres, the TG 1-3 repeat binding protein Rap1 is essential for Sir protein recruitment, but recent studies show that the Ku heterodimer also plays an important role in promoting SIR recruitment, which is counteracted by other factors (5). The subsequent assembly of Sir2͞3͞4 complexes along the adjacent nucleosomes is thought to be driven by a network of interactions between the SIR proteins (6) and a set of critical contacts between both Sir3p and Sir4p and the N-terminal tails of the core histones H3 and H4 (7).…”
mentioning
confidence: 99%